Ferroptosis-immune crosstalk in cervical cancer: mechanisms and therapeutic implications - Li, Lili; Bo, Yunfeng; Xue, Dan; Qin, Lijuan (Frontiers in Immunology, 2025)
Cervical cancer remains a leading cause of cancer-related mortality in women worldwide, particularly in regions with limited access to screening and vaccination. While immunotherapy has shown promise in treating advanced cervical cancer, immune evasion mechanisms within the tumor microenvironment continue to limit therapeutic efficacy. Ferroptosis, a form of iron-dependent regulated cell death characterized by lipid peroxidation, has recently been recognized as a crucial regulator of tumor progression and immune modulation. Emerging evidence suggests that ferroptosis interacts with immune signaling pathways, contributing to immune suppression, antigen presentation defects, and the remodeling of the tumor immune microenvironment in cervical cancer. This review highlights the current understanding of ferroptosis-related mechanisms underlying immune evasion in cervical cancer, including alterations in ferroptosis regulators, redox imbalance, and ferroptosis-induced release of immunomodulatory molecules. We further explore how targeting ferroptosis may enhance anti-tumor immunity and overcome resistance to immunotherapy. Finally, we discuss recent advances in ferroptosis-based therapeutic strategies and identify future directions for integrating ferroptosis modulation into cervical cancer treatment.